Pengaruh Ukuran Partikel dan Laju Alir Terhadap Biosorpsi Ion Cu(II) Menggunakan Biosorben Kulit Langsat (Lansium domesticum) - Hardianti, Amirah Salsabila; Kurniawati, Desy; Etika, Sri Benti; Sanjaya, Hary (Periodic, 2024)
Cu2+ ion is a dangerous metal ion produced from various industrial wastes that need to be addressed. Excess and high concentrasions of absorbed Cu2+ ions can disrupt health and ecosystems because they are difficult to degrade and easily accumulate in the body. This study aims to determine the optimum conditions for the absorption of Cu2+ ions using langsat fruit peel on the effect of particle size and flow rate by column method. Adsorption of Cu metal ions with langsat fruit peel biosorbent obtained optimum conditions at adsorbent particle size of 150 micrometers with adsorption capacity of 13,963 mg/g and flow rate of 1 mL/minute with adsorption capacity of 13,442 mg/g. This shows that langsat fruit peel is one of the best biosorbents in absorbing metals with large absorption capacity data.